2021
DOI: 10.3389/fpsyg.2020.570534
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Implicit Link Between Red and Aggressiveness as Well as Blue and Agreeableness

Abstract: Previous studies have found a link between red and aggressive behavior. For example, athletes who wear red uniforms in sports are considered to have a competitive advantage. So far, most previous studies have adopted self-report methods, which have low face validity and were easily influenced by the social expectations. Therefore, the study used two implicit methods to further explore the association between red and aggressiveness. A modified Stroop task was used in Experiment 1 to probe college students’ diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Third, we show that the most effective forms of failure messaging feature failures that are attributed to unstable (i.e., temporary) causes that reside within consumers, which can guide testimonial ad design. Finally, based on our theorizing, the effect of failure messaging on consumers’ brand interest is contingent on the associations between the brand and aggression; thus, feminine brands that cue aggression through strategies such as incorporating aggressive design elements (e.g., the color red; Geng, Hong, and Zhou 2021) can successfully employ failure messaging to promote the brands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, we show that the most effective forms of failure messaging feature failures that are attributed to unstable (i.e., temporary) causes that reside within consumers, which can guide testimonial ad design. Finally, based on our theorizing, the effect of failure messaging on consumers’ brand interest is contingent on the associations between the brand and aggression; thus, feminine brands that cue aggression through strategies such as incorporating aggressive design elements (e.g., the color red; Geng, Hong, and Zhou 2021) can successfully employ failure messaging to promote the brands.…”
Section: Discussionmentioning
confidence: 99%
“…In the ads, participants read a college student's testimonial about how wearing an infinity bracelet bought from Hestia Crafts reminds the student to learn from failures (vs. successes) and move forward (see Web Appendix E). In the ads, the brand logo was displayed once in red (hue: 0, saturation: 240, lightness: 120) and once in blue (hue: 160, saturation: 240, lightness: 120), as prior research shows that these specific colors evoke perceptions of aggression and agreeableness, respectively (Geng, Hong, and Zhou 2021). Participants expressed their interest in buying products from Hestia Crafts (“How interested are you in buying a product from this brand?”; nine-point scale anchored at “not interested” and “very interested”).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study failed to clarify whether the red uniform reduced the performance of the opponents or improved the performance of the wearers. Later studies confirmed the association between red and aggressiveness (Geng et al, 2021), and found that the red-aggressiveness link affects observers' subjective judgments (e.g., that of referees) (Hagemann et al, 2008;Krenn, 2014Krenn, , 2015. Based on the redaggressiveness link, it seem to suggest that red affect observers' (referees) judgment of competitive performance, but it not answer the question of how red affect opponents' motor behavior.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation has to do with the biologically based responses to the color red. Red may enhance practitioners’ ratings by presenting biologically based signals of aggressiveness and dominance [ 28 , 46 , 47 ]. The effect of the red uniform is in line with the nature of Wushu, which portrays aggression, albeit in a stylized, aesthetically pleasing form.…”
Section: Discussionmentioning
confidence: 99%